Lanthanum promoted cobalt catalyst for methane dry reforming - Ong, Chen Loong (2014)
In the present work, different loadings of lanthanum cobalt based catalyst for the dry reforming reaction was studied. The BET specific surface area has declined with the increment of La loading although pore volume increased significantly beyond 1wt% La doping. 5wt% La-Co/MgO catalyst has BET specific surface area of 31.67 m²g-1 and 0.30 cm3g-1 of pore volume. From FESEM imaging, an addition of lanthanum promoter has created solid with smaller particle size. This is consistent with XRD analysis where crystallite size significantly dropped when the percentage of La was higher. XRD shows that the peaks representing CO3O4 occurred at 20=36.94° and MgO or Co/MgO at 20=42.94°, 62.32°, 74.74°and 78.64°. As lanthanum loading increases, the crystallite size dropped from 24.5nm to 17.9nm at peak 20=42.94° while the crystallite size decreased from 23.5nm to 17.1nm at peak 20=62.32°. Reaction studies have found that 5wt% La catalyst gave the highest rate formation of product yield (H2 and CO) However; the composition of products yield was quite low. It was about 1.6%. It was then employed for further reaction studies. The rate was optimum at CO2:CH4 feed ratio of 0.67. Next, when reforming temperature was increased, the reaction rate also increased. The activation energy obtained was 82.26 kJ mol-1